2014
DOI: 10.1111/jop.12221
|View full text |Cite
|
Sign up to set email alerts
|

Association between human papilloma virus/Epstein–Barr virus coinfection and oral carcinogenesis

Abstract: Background The recent epidemic of head and neck squamous cell carcinomas (HNSCC) associated with human papilloma virus (HPV) has not addressed its association with lymphoid tissue in the oropharynx or the potential role of Epstein-Barr virus (EBV)/HPV co-infection. Methods The prevalence of HPV and EBV infection/co-infection and CD21 mRNA expression were determined in normal and cancerous tissues from the oropharynx using in situ hybridization (ISH), p16 and quantitative reverse transcriptase PCR (qRT-PCR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 28 publications
7
89
0
Order By: Relevance
“…Some studies have detected the presence of both viral genomes in oral squamous cell carcinomas [19, 20] and nasopharyngeal carcinomas [21], and Jiang et al found a significant association of the presence of EBV and HPV together in oropharyngeal cancers of the tonsil and base of tongue [20]. In addition, Shimabuku et al [22] found that co-expression of EBV latent membrane protein-1 and HPV 16 E6 in primary mouse fibroblasts induced anchorage-independent growth and caused tumor formation in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have detected the presence of both viral genomes in oral squamous cell carcinomas [19, 20] and nasopharyngeal carcinomas [21], and Jiang et al found a significant association of the presence of EBV and HPV together in oropharyngeal cancers of the tonsil and base of tongue [20]. In addition, Shimabuku et al [22] found that co-expression of EBV latent membrane protein-1 and HPV 16 E6 in primary mouse fibroblasts induced anchorage-independent growth and caused tumor formation in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…EBV-HPV co-infection was observed in half of the samples, which supports the hypothesis of Kumar et al, 5 which proposes that infection by multiple oncogenic viral agents acts as an important risk factor in oral carcinoma. Similarly, Jiang et al 29 suggest that co-infection may have a bigger effect on invasion than on proliferation.…”
Section: 23mentioning
confidence: 99%
“…Next, we examined the EBV latent gene expression program of the EBV-positive FaDu cell lines. The FADu-EBV and FaDu-HE were previously shown to express equal levels of LMP2 mRNA [4]. Both FaDu-EBV and FaDu-HE were positive for LMP1 mRNA, but levels differed between the two EBV-positive cell lines (Figure 1).…”
Section: Resultsmentioning
confidence: 87%
“…Co-infection of HPV and EBV has been reported in nasopharyngeal, hypopharyngeal and oral cancers. Recently, we have shown that co-infection of these viruses in lymphoid rich sites (tonsil and BOT) of the head and neck is significantly associated with cancer status [4]. Head and neck tobacco associated cancers are recalcitrant to treatment because of multiple mutations that limit the identification of specific molecular targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation